Repeated Restraint and Nerve Growth Factor Administration in Male and Female Mice: Effect on Sympathetic and Cardiovascular Mediators of the Stress Response - Manni, Luigi; Fausto, Veronica D.; Fiore, Marco; Aloe, Luigi (Current Neurovascular Research, 2008)
Chronic stress and increased sympathetic nerve activity have been associated with cardiovascular disorders such as hypertension, myocardial infarction and stroke. The aim of this study was to investigate the role of nerve growth factor (NGF) on the expression of tyrosine hydroxylase (TH), vascular-endothelial growth factor (VEGF) and leptin receptor (OB-R) in brain, adrenal and cardiovascular tissues of adult male and female mice following a chronic stress procedure. It was found that daily restraint for 10 consecutive days alters TH levels in hypothalamic and brainstem areas related to sympathetic activation, in both male and female mice. Chronic stress procedure also modifies heart and aorta VEGF levels in male mice, and adrenal glands TH in female mice. The NGF administration in stressed mice reverted the stress-induced up-regulation of TH levels in male and female mice hypothalamic nuclei and in male locus coeruleus. Administration of NGF in stressed animals also down-regulated OB-R levels in the hypothalamus of both male and female mice and in the female aorta. Our findings indicate that repeated restraint in mice has an effect on TH and VEGF protein content at different brain and peripheral sites involved in the sympathetic and cardio-vascular response to stressful stimuli. NGF administration is able to counteract some of these stress-induced changes. Since NGF is known to be up-regulated during stress, a possible functional significance of our observations is that the circulating NGF released during and following stress may serve to prevent possible deficits and/or damage linked to stress-induced sympathetic and cardiovascular activation.
Keywords: VEGF